Mini-review: Epidemiology and zoonotic potential of multiresistant bacteria and Clostridium difficile in livestock and food - Dahms, Carmen; Hübner, Nils-Olaf; Wilke, Florian; Kramer, Axel (German Medical Science GMS Publishing House, 2014)
[english] Aim: Information on the epidemiology of multiresistant bacteria (MRB) with zoonotic potential is growing but still remains quite incomplete. This narrative mini-review provides a general overview of the epidemiology of the most important zoonotic MRB in cattle, swine and poultry in Europe.Methods: A literature search was conducted mainly on the PubMed website including articles published until April 2012. Results: Livestock-associated methicillin-resistant (LA-MRSA) especially poses a zoonotic risk to people working in close contact with livestock. These people may become carriers themselves and the hazard of transmission into health-care facilities needs surveillance. Extended-spectrum beta-lactamases (ESBL) producing bacteria are widely spread in both humans and livestock, sharing similar genotypes, especially of the CTX-M-group, which makes a zoonotic transfer very likely. Identical strains of vancomycin-resistant enterococci (VRE) were found both in humans and animals, after ingestion of animal strains transient colonization of the human gut may be possible. Only a few data are available on the transmission of methicillin-resistant coagulase-negative staphylococci (MR-CoNS) between humans and animals. Direct contact to colonized animals may be a risk factor as well as the exchange of resistance genes between human and animal staphylococci. () ribotype 078 emerges in livestock and humans and a zoonotic transmission seems probable as genotypes and diseases resemble each other.Conclusion: All discussed MRB and are important nosocomial agents which also occur in livestock and were found in foods of animal origin. Further analysis is needed to reveal the exact transmission routes and to perform a reliable risk assessment.